La société multiculturelle selon Jürgen Habermas (I) - Denis Goeldel (Recherches Germaniques)
This paper analyzes Jürgen Habermas’ conception of multiculturalism in the early 1990s, following the migratory movements caused by the break-up of the Soviet bloc and Yugoslavia, and the emergence of an ethnic neo-nationalism in Reunited Germany. In Republican Integration (1998), Habermas develops the idea of “integrating the other in his otherness” and “with equal rights”. He suggests two levels of integration: a first level, that of the “ethical integration” of groups and subcultures with their own “forms of life”, which are preserved in the host country; a second level, that of “political integration”, where the newcomers are asked to adhere to the constitutional principles underpinning the “common political culture”. The article highlights a “liberal” type of multiculturalism, opening the borders to any foreigner who wishes to immigrate—Habermas speaks of a “right to immigration” and a “right to integration”—in exchange for his “acculturation” to the “common political culture” of the host country, culminating in the “realistic utopia” of a “cosmopolitan state”, in which every “world citizen” is ensured to benefit from an “effectively institutionalized cosmopolitan right”.